Protective Effect of Mycosporine-like Amino Acids Isolated from an Antarctic Diatom on UVB-Induced Skin Damage - Kai Wang; Yashan Deng; Yingying He; Junhan Cao; Liping Zhang; Ling Qin; Changfeng Qu; Hongmei Li; Jinlai Miao (International Journal of Molecular Sciences, 2023)
Although it is well recognized that mycosporine-like amino acids (MAAs) are ultraviolet (UV) protective agents that can reduce UV damage, the specific biological mechanism of its role in the skin remains unclear. In this study, we investigated the effect of MAAs extracted from Antarctic diatom Phaeodactylum tricornutum ICE-H on UVB-induced skin damage using a mice model. The MAAs components identified by liquid chromatography-tandem mass spectrometry included 4-deoxygadusol, shinorine, and porphyra-334, which were purified using a Supledean Carboxen1000 solid phase extraction column. The antioxidant activities of these MAA compounds were tested in vitro. For UVB-induced skin photodamage in mice, MAAs alleviated skin swelling and epidermal thickening in this study. We detected the content of reactive oxygen species (ROS), malondialdehyde, and collagen in skin tissue. In addition, quantitative real-time polymerase chain reaction was used to detect nuclear factor-κB (NF-κB), tumor necrosis factor α, interleukin-1β, cyclooxygenase-2, mitogen activated protein kinase (MAPK) family (extracellular signal-regulated kinase, c-Jun amino-terminal kinase, and p38 kinase), and matrix metalloproteinases. The expression of these cytokines and enzymes is related to inflammatory responses and collagen degradation. In comparison to the model group without MAA treatment, the MAA component decreased the concentration of ROS, the degree of oxidative stress in the skin tissue, and the expression of genes involved in the NF-κB and MAPK pathways. In summary, these MAA components extracted from Phaeodactylum tricornutum ICE-H protected against UVB-induced skin damage by inhibiting ROS generation, relieving skin inflammation, and slowing down collagen degradation, suggesting that these MAA components are effective cosmetic candidate molecules for the protection and therapy of UVB damage.